Global Waste Management Outlook - United Nations Environment Programme (United Nations, 2016)
The Global Waste Management Outlook is the first comprehensive, impartial and in-depth assessment of global waste management. It reflects the collective body of recent scientific knowledge, drawing on the work of leading experts and the vast body of research undertaken within and beyond the United Nations system. The six chapters inform the reader about trends, provide an analysis on governance and financial mechanisms, and offer policy advice on the way forward. The main document targeting professionals is accompanied by two summary documents, one for decision makers and the other for the public more broadly. This Global Waste Management Outlook offers a profound analysis of the enormous potential better waste management provides to assist in meeting the sustainability challenges ahead.